On the accuracy, reliability and controllability of impact tests of RC beams - Hao, Hong; Tran, Tung; Li, Huawei; Pham, Thong; Chen, Wensu (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The impact response of reinforced concrete (RC) beams has been intensively investigated by impact tests with various setups. Given the same impact energy, different setups of drop-weight impact tests might lead to different measurements and observations of identical RC beams including the impact force, reaction force and displacement, implying the obtained impact test results depend on not only the impact energy and structure itself, but also the test setups. Therefore, it is essential to understand the measurement accuracy, reliability, and controllability of drop-weight impact tests for a successful impact test design and interpretation of test results on RC beams. This study examines the effects of various test setups and critical factors on the impact response of RC beams. Recommendations for the processing and interpretation of test results with respect to the configuration of the test setup, including the location of load cells, mass and shape of the impact head, interlayer, and boundary condition are made for drop-weight tests. The mechanism of the negative reaction force often observed in impact tests has been unveiled for a better understanding of the impact problem.